Outcomes of atrial arrhythmia radiofrequency catheter ablation in patients with Ebstein's anomaly. Issue 3 (27th February 2017) - Hassan, Abdalla; Tan, Nicholas Y; Aung, Htin; Connolly, Heidi M; Hodge, David O; Vargas, Emily R; Cannon, Bryan C; Packer, Douglas L; Asirvatham, Samuel J; McLeod, Christopher J
Abstract: Aims: Atrial arrhythmias are common in patients with Ebstein's anomaly (EA) despite cardiac surgical repair and concomitant Maze procedures. We aimed to evaluate the outcome of radiofrequency catheter ablation in this group of patients. Methods and results: All patients with EA and atrial arrhythmias who underwent catheter ablation for atrial arrhythmias between 1/1999 and 1/2016 were included. Atrial arrhythmia recurrence was identified as the primary outcome; secondary outcomes included repeat ablation, need for antiarrhythmic medications after ablation, and death. Predictors of recurrence were sought using univariate analysis. 22 patients (median age 42 years, 54.5% male) were included. Atrial flutter was the most common presenting arrhythmia ( n  = 14 patients, 63.5%), whereas focal atrial tachycardia (FAT) and atrial fibrillation were identified in 5 (22.7%) and 2 patients (9.1%), respectively, with both atrial flutter/fibrillation evident in a single patient 1 (4.5%). 8 patients (36.4%) had a history of right-sided maze procedures. Cavotricuspid isthmus atrial flutter (CTI-AFl) was the most commonly induced arrhythmia ( n  = 13, 59.1%), followed by incisional intra-atrial re-entrant tachycardia (IART; n  = 4, 18.2%), and FAT ( n  = 4, 18.2%); 3 patients also underwent left-side ablation with concomitant pulmonary vein isolation (13.6%). 1-year and 5-year atrial arrhythmia recurrence rates were 10.0% and 41.2%, respectively. 7 patients (31.8%) underwent redo ablations, and anti-arrhythmic medication was utilized in 8 patients (36.4%) post-ablation. Neither ablation location nor echocardiographic parameters were found to be predictors of arrhythmia recurrence. Conclusion: Catheter ablation of atrial arrhythmias in patients with EA has a favorable outcome overall with an acceptable recurrence and safety profile; left-sided ablations are rarely necessary. Despite prior Maze and catheter ablation procedures, CTI-AFl and IART recurrences predominate.